Sitting vs. Standing in VR: Towards a Systematic Classification of Challenges and (Dis)Advantages - Zielasko, Daniel; Riecke, Bernhard E. (SeatedVR: 1st Workshop on Seated Virtual Reality at IEEE VIrtual Reality, 2020)
With this work, we propose a draft classification of advantages and disadvantages between sitting and standing user interfaces in VR to stimulate discussion and future work.
Keywords: 2-page conference paper; NSERC DG 2026; Riecke; Riecke_2020; bernhard-riecke; conferencePaper; conferencePapers; daniel-zielasko; locomotion; short conference paper